Challenges Facing Teenage Mothers in School, Teachers’ Perspective: The Case of WA West District - Adangabe , Amos Amuribadek (South Asian Journal of Social Sciences and Humanities, 2020)
Bearing children as a young teenager is normally connected with various interruptions for young  ladies with regards to class participation. The young mothers’ who are in school are left to unwind  the interruptions some of the time all alone. Denying them the help they have to seek after their  schooling sentence them and their infants to an endless loop of neediness and obliviousness. In the  event that society anticipates that the young ladies should be effective with tutoring, there must be  arrangement that objectives their exceptional instructive requirements. The study explored the  perception of educators about the difficulties confronting adolescent moms in school in the WA West District. The purposeful sampling technique was used in selecting the teachers involved. A  focused group discussion was used in gathering and data analysis was done thematically. While  the results indicate that, majority of the teenage mothers in school are mostly tired even before  they come to school, it further revealed that the majority of the teachers perceive teenage mothers  having low self-esteem, poor time management, role conflict and how they are supported were  among the things discussed. The recommendations to tackle these perceptions were made.
Keywords: Teenage Mothers; School; Teachers